A linguagem como forma de violência na relação professor-aluno em sala de aula - Cantarelli, Juliana Mezomo (2012)
This paper is linked to the Line of Practical School Researches and Public Policies of the Post-Graduation Program at the federal University of Santa Maria. The current study belongs to the Moral Affection Research Group and its main project The conflicts and sentiments present in the pedagogical relationship and their networks in the construction of moral personality . The theme arises from my own experiences as a student of basic education and also graduation. Later, as a professor I started reflecting about the relations among teachers and students. Thus, this research aims to investigate how the language used by the teacher in classroom might be understood as a form of violence from the teacher to his/her pupils, to identify how the teachers understand how their languages might be a form of violence towards their students and to verify how the students see this violent language used in classroom. The methodology adopted presents a qualitative approach under the perspective of a study case with a teacher who teaches the third grade fundamental school and with her pupils. The study was carried out in a state school of basic education in the central region of Rio Grande do Sul state. The data collection was made by means of direct observations in classrooms. The data were recorded on a field diary and in a semi-structured interview with the class teacher and her students. The study was divided in three chapters: The first one: Delimitation and fundaments of investigation , which delimits and specifies the theme area of investigation, the questions of a research and their reasons as well as the methodological approach of it. In chapter 2: The construction of thinking, language and morality in children , where it was analyzed the construction and the development of language related to the thinking and notion of morality for children. To do so, it was used, as a theoretical support, the studies carried out by Jean Piaget. In chapter 3: The violence and its imbrications in teacher s and student s relations . It is divided into two sub-chapters. In the first one, it was checked out the relations of teachers and students in classroom. In the second one the violence inside this relation was highlighted. The theoretic fundament of this paper comes from: Alícia Fernandez, Julio Groppa Aquino, Maria Teresa Estrela, Ulisses F. de Araújo, Xus Martín Garcia, Josep Maria Puig e Yves de La Taille. Based on the data analysis, it is concluded that how language is used by the teachers, consciously or not, might be understood as a form of violence and that the students perceive this kind of language as a form of violence as well. However, for the teachers, their languages are not seen as a form of violence once they serve to shape their students behavior, to impose limits so that they become civilized and polite people. Acting like this is necessary, acceptable and, therefore, normal.